Effect of asfotase alfa in the treatment of hypophosphatasia- A systematic review - N Jaswanthi; R Sindhu; P Nimmy; D Prabu; M RajMohan; V V Bharathwaj; Dinesh Dhamodhar; S Sathiyapriya (Wolters Kluwer Medknow Publications, 2023)
Hypophosphatasia (HPP) is a life-threatening disease that occurs due to the mutation of the TNSALP (Tissue nonspecific isoenzyme of alkaline phosphatase) encoding gene. There is no approved treatment for Hypophosphatasia. Therefore, the only effective treatment for HPP is enzyme replacement therapy using the drug asfotase alfa which increases the patient's life span. The aim of the study is to evaluate the effectiveness and safety of asfotase alfa (enzyme replacement therapy) in treating HPP. A Literature search was done using PubMed, Google scholar, science direct, and Wiley LILACS utilizing MeSH keywords such as - Hypophosphatasia and asfotase alfa. A total of 411 articles were screened, of which four articles were taken for this qualitative analysis. Reporting of this systematic review is done by using PRISMA guidelines. Asfotase alfa/enzyme replacement therapy is examined on patients with different age groups and on congenital HPP patients to assess the effectiveness of HPP treatment. Enzyme replacement therapy using asfotase alfa is an effective and assured treatment for infants, children, and adults suffering from HPP.